Effect Of Earthquake Forces On Columns With Different Strengthening Using Sap2000 Software - Purba, Sadvent; Wijaya, Nehemia (JURNAL TEKNIK SIPIL CENDEKIA (JTSC), 2025)
Indonesia is an area that has quite a high frequency and strength of earthquakes because it is at the meeting point of four tectonic plates, namely the Eurasian plate, the Indo-Australian plate, the Pacific plate and the Philippine Sea plate. Earthquake-resistant buildings are an alternative to minimize the impact of earthquake forces that occur. One design that needs to be analyzed is that there are openings in the building wall structure that cause the columns not to bend properly when receiving lateral forces, so they have the potential to fail. A collapsing column will cause the load of the building floor above it to collapse. Through this research, the influence of the frequency of earthquake forces, the influence of earthquake forces on the deviation between floors, and the location of the collapse in building models A (without walls) and B (with walls) will be identified. The method used is dynamic load analysis in SAP2000 based on spectrum response. Based on the results of the SAP2000 analysis, it can be seen that the deviation value between floors is smaller in building model B (with walls), thus indicating short column with lower heights absorb more energy and have stiffer properties. The location of the collapse is not visible in the SAP2000 analysis, but the largest deformation occurs in the beam for both building models.